Pembuatan Biodegradable Film dari Pati Biji Nangka (Artocarpus hetrophyllus) dengan Penambahan Kitosan - Betty Ika Hidayah (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Biodegradable film is thin layers made of natural and renewable materials which can be easily decomposed by microorganisms. Starch is one of polysaccharide that can be used as a film. Jackfruit seeds have a starch content of 70.26%. Film of starch has low barrier properties against water, so it need addition of hydrophobic substances such as chitosan. This studyaims to determine the effect of jackfruit seeds starch with or without of chitosan mixture on the characteristics of biodegradable film. Films were produced using jackfruit seed starch with the composition variation is 2 g, 3g, 4g in 50 ml aqueous and chitosan withthe composition variation is 0,5g, 1 g, 1,5g in 50 ml of 1% acetic acid solution. Then in an oven at 50 ° C for 24 hours. These results indicate that the making of the film without chitosan does not affect the thickness, water content, melting point, and solubility significantly. But, affect the degradation of the film with EM4, amounting to 43.33% at 4 g starch and degraded in the soil for 2 weeks. Meanwhile, mixing of chitosan significantly affect the thickness, water content, melting point, solubility and degradation by microorganisms. This is shown with the smallest percentage of jackfruit seeds starch in the composition of 2 g, 3 g and 4 g, is 26.22%, 30.33% and 15.89%, and can be degraded after 3 weeks in the soil.